Variety of Photographers Languages in Jombang District Sociolinguistic Study - Faris Ihsan Syafri, Ahmad (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Humans cannot be separated from communicating with each other to convey a specific purpose or purpose to communicate in an activity such as trade, economic activity, educational activity, and certain events and activities in everyday life. Tools that are often used by humans in interacting is language. Sociolinguistics is a branch of linguistics that is interdisciplinary in sociology and linguistics which discusses the interrelationships of language factors in speech communities. Every profession certainly has a distinctive language that is used according to the conditions and requirements of the job. The diversity/types of language used in situations, circumstances, or for certain purposes is called a variety of languages. And the variety of languages ​​arises because of the speakers' need for communication tools that are appropriate to the situation in a particular context. In a society there are various activities, one of which is photography. Photography is a medium that can be used to capture a phenomenon or the importance of an event. In photography activities there must be a photographer. Photographers are actors/people who try to produce images by capturing light using a camera or other photographic equipment. The purpose of this study is to find, analyze and describe the variety of languages ​​used by photographers in Jombang district. This type of research is a qualitative descriptive research and uses participatory observational research techniques and documentation, records and notes so that it can be seen that (1) the variety of languages ​​used by photographers in Jombang district includes register forms and register functions. (2) while the variety of languages ​​used by photographers in Jombang district includes register forms and register functions. The photographer's language in terms of formality includes familiar languages, casual languages ​​and business/consultative languages.